Genetic features of multicentric/multifocal intramucosal gastric carcinoma. Issue 8 (3rd July 2018) - Mizuguchi, Aya; Takai, Atsushi; Shimizu, Takahiro; Matsumoto, Tomonori; Kumagai, Ken; Miyamoto, Shin'ichi; Seno, Hiroshi; Marusawa, Hiroyuki
Abstract : Chronic gastritis caused by Helicobacter pylori ( H. pylori) infection could lead to the development of gastric cancer. The finding that multiple gastric cancers can develop synchronously and/or metachronously suggests the development of field cancerization in chronically inflamed, H. pylori ‐infected gastric mucosa. The genetic basis of multiple tumorigenesis in the inflamed stomach, however, is not well understood. In this study, we analyzed the microsatellite instability (MSI) status and copy number aberrations (CNAs) of 41 multiple intramucosal early gastric cancers that synchronously or metachronously developed in 19 patients with H. pylori infection. Among the 41 intramucosal gastric carcinomas, 9 (22%) exhibited MSI, and the remaining 32 (78%) exhibited the microsatellite stable (MSS) phenotype. Metachronous multiple intramucosal gastric carcinoma exhibit inter‐tumor heterogeneity by individually acquiring genetic aberrations. All synchronous multiple intramucosal gastric carcinoma pairs shared a common MSI/MSS profile, and CNA analysis revealed that synchronous multiple intramucosal gastric carcinoma pairs with the MSS phenotype shared common aberrations of representative tumor‐suppressor genes, including focal deletion of APC, TP53, CDKN2A, and CDKN2B . Multiregional CNA analysis revealed that heterogeneous gene amplifications/deletions, including PDL1 amplification, evolved under the presence of shared "trunk" genetic alterations in a subpopulation of individual intramucosal gastric carcinomas. These data suggest that multiple gastric carcinomas develop in a multicentric/multifocal manner exhibiting features of inter‐ and intra‐tumor heterogeneity in H. pylori ‐infected gastric mucosa, whereas synchronous multiple intramucosal gastric carcinomas could share partially common genetic alterations, possibly via common oncogenic pathways. Abstract : What's new? Inflammation caused by H. pylori infection can lead to gastric cancer. Here, the authors investigated what happens genetically when multiple tumors arise, either at the same time (synchronous) or over a longer period (metachronous). They compared genetic characteristics between multiple intramucosal gastric carcinomas, as well as within individual tumors. Pairs of synchronous carcinomas shared deletions of certain tumor suppressor genes, suggesting they arose along the same pathway. Metachronous carcinomas showed a variety of copy number variations, suggesting they each arose independently. They also observed a certain amount of genetic variation within tumors, including mutations that help stave off immune attack.